Abnormal muscle in the anterior compartment of the forearm: a case report - Rodrigues, Vincent (BioMed Central, 2009)
During routine dissection for the undergraduate medical students, we encountered an unusual, additional muscle in the anterior compartment of the forearm. This muscle took origin from the anterior surface of the radius in common with the flexor digitorum superficialis muscle. It had a tendon of origin and a tendon of insertion. Its fleshy radial belly and the tendon of insertion, crossed superficial to the median nerve. The muscle was inserted partly to the flexor retinaculum and partly to the undersurface of palmar aponeurosis. The observations made by us in the present case will supplement our knowledge of variations of the muscles in this region which could be useful for hand surgeons as it could possibly compress the median nerve because of its close relationship to it.